Keys to Attracting Private Capital for Railway Development - Lawrence, Martha; Ollivier, Gerald (World Bank Group, Washington, DC, 2015)
Two of the largest railway systems in the world, China’s and India’s, have intensified their focus on the private sector as an indispensable source of capital to help them enlarge their rail capacity. They will find promising options if they recognize the common characteristics of successful efforts, both in their railways and elsewhere: profitability, manageable risks shared appropriately, and shared gains. Even unprofitable rail activities, such as commuter transit, can attract private capital if adequate public subsidies are in place.